Public responsibility and shortage of resource in healthcare - Lasker, Shamima Parvin (Bangladesh Journal of Bioethics, 2012)
DOI: http://dx.doi.org/10.3329/bioethics.v2i3.10265 Bangladesh Journal of Bioethics 2011;2(3):19-20